An effective Fe(ii) doping strategy for stable and highly photoluminescent CsPbBrI2 nanocrystals. Issue 13 (7th March 2022) - Chen, Yanbin; Yang, Hewei; Song, Jian; Zhang, Bao
Abstract : Iron dopants (FeBr2, FeAc2, and FeF2 ) have been used to modify the performance of red CsPbBrI2 perovskites, and stable and highly photoluminescent Fe 2+ doped CsPbBrI2 nanocrystals were obtained. Abstract : Doping metal ions into a perovskite lattice is an effective strategy for tailoring the intrinsic properties of perovskite nanocrystals (NCs). Herein, strong red-emitting and highly ambient and light stable Fe 2+ -doped CsPbBrI2 NCs with a maximum photoluminescence quantum yield (PLQY) of 92.1% were obtained. Systematic investigation of Fe 2+ doping on the stability and the luminescence performance of CsPbBrI2 NCs was performed. Owing to the smaller ionic size compared to Pb 2+, Fe 2+ induced the lattice contraction and shortened the bond length of Pb–X, which suppressed the distortion of [PbX6 ] 4− octahedra, thus improving the stability of CsPbBrI2 NCs. The champion sample could maintain up to 86% emission under the ambient conditions for 5 weeks. Besides, the incorporation of Fe 2+ suppressed the formation of halide vacancies and optimized the relaxation process of CsPbBrI2, thereby contributing to the enhancement of PLQY. This facile Fe 2+ doping method provides an effective strategy to synthesize stable and highly photoluminescent red perovskite materials.